Doses de zinco e nitrogênio na produtividade e qualidade de grãos de ervilha - Cardoso, Eliana Duarte; Haga, Kuniko Iwamoto [UNESP]; Binotti, Flávio Ferreira da Silva; Filho, Walter Veriano Valério [UNESP]; Nogueira, Débora Cristiane [UNESP] (FapUNIFESP (SciELO), 2012)
Peas present a potential to be cultivated in the winter, in Brazil, and also a great importance, especially in human feeding, due to its high protein content. However, its yield is still low and there are just a few studies aiming at improving pea grains quality and yield. This study aimed at evaluating the nitrogen and zinc fertilization effect on the pea grains (Utrillo cultivar) chemical quality and yield. The experiment was carried out in a dystrophic clayey Latosol-Haplustox, in Selvíria, Mato Grosso do Sul State, Brazil, in 2005. A randomized blocks design was used, in a 4×4 factorial scheme, totaling 16 treatments and 3 replications, including four nitrogen doses (0 kg ha-1, 60 kg ha-1, 120 kg ha-1, and 240 kg ha-1), as urea, via ground, at 30 days after sowing (DAS), and four zinc doses (0 kg ha-1, 1,5 kg ha-1, 3 kg ha-1, and 6 kg ha-1), as zinc sulphate, via leaf, at 45 DAS. The combination of zinc and nitrogen doses improved the grains chemical quality. Zinc had no effect on grain yield, however, high nitrogen doses negatively affected yield.
Zinc and nitrogen doses on pea grains quality and yield
Keywords: Amino acid; Carbohydrate; Pisum sativum L.; Protein; Pisum sativum